FRI0454 Disease Flares and Persistent Low-Level of Disease: Long-Term Outcome in A Cohort of Patients with BehÇEt's Disease. (10th June 2014) - Stagnaro, C.; Talarico, R.; Ferrari, C.; d'Ascanio, A.; Tavoni, A.; Elefante, E.; Tani, C.; Baldini, C.; Mosca, M.; Bombardieri, S.
Abstract : Background: Behçet's disease (BD) is a multisystemic, chronic relapsing inflammatory disease classified among the vasculitis. Neurological and eye involvement are two of the most serious manifestation of BD and both still represent significant causes of morbidity. Objectives: The primary aim of the study was to evaluate the long-term outcome in a cohort of patents with BD; the secondary aim was to explore any potential correlation between long-term outcome and demographic and clinical profile. Methods: The study enrolled 117 patients, all fulfilling the International Study Group (ISG) criteria for BD. One hundred and seventeen patients were retrospectively studied. The male/female ratio was 1.6:1, with a mean disease duration of 11±5 years. Their mean age was 42±9 years (min:18, max:77), while the mean age at disease onset was 25±4 years. The mean ± SD duration of follow-up at our centre was 10±2 years. Long-term outcome was evaluated by means of disease flares according the BD Current Activity Form (BDCAF), persistent low-level of disease (defined as a level minimal activity of disease requiring only low-medium doses of corticosteroids), and disease damage according the Vasculitis Damage Index (VDI). The statistical analysis was performed using Student t-test, Mann-Whitney-U test, ANOVA and Pearson correlation Results: The main clinical features presented during the follow-up by the cohort were: mucocutaneous involvement (100%), joint involvement (49%), ocular involvement (40%), neurological involvement (38%), vascular thrombotic events (22%), gastro-enteric involvement (16%). Globally, we observed 105 episodes of disease flare, of which: 25% of patients with neurological involvement, 60% of ocular involvement, 50% of muco-cutaneous involvement, 12% of joint involvement, 50% of vascular involvement and 28% of gastro-enteric involvement. Thirty-three patients presented a persistent low-level disease, that required a medium corticosteroids dose of 4 mg of 6-methylprednisolone. Moreover, 39 patients presented a VDI >1. A significant correlation was found between disease flares and younger age and male sex; persistent low-level of disease and disease damage resulted significantly associated with early onset of disease and high number of disease flare in the first 2 years of disease. Notably, persistent low-level of disease and disease damage resulted inversely correlated with the use of anti TNF alpha agents, independently of the type of organ involvement. Conclusions: As literature data suggest, a specific demographic profile exists of poor outcome in BD, represented by young males. The use of anti TNF alpha agents is associated with a positive effect on maintaining remission of disease, most likely due to their steroid sparing effect. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5696